Disability as a result of affective disorders in the Irkutsk region referral to 107 the bureau of medical-social expertise - O. V. Petrunko; O. G. Klimenko (Acta Biomedica Scientifica)
The data of the study by continuous total disability due to affective disorders of the adult population in the Irkutsk region referral to the bureau of medical-social expertise in 2007—2011 years were presented. Intensive index was calculated per 1000 population (level). The percentage of primary disability for 5 years was 18,5 %, whereas redisability (81,5 %) prevailed. The level of total disability due to affective disorders has decreased from 0,16 in 2007, 0,18 in 2008 to 0,14 in the years of the period. People of working age were 82,5 % disabled due to affective disorders, while the retirement age - only 17,5 %. The mean total disability in working age (16,5) exceeded the rate of retirement age (11,5 per 1000). Women predominated, among the disabled. The level of total disability in men was more than two times lower.